Improving The Speaking Ability Of XII IPA 1 Students Of SMAN 4 Oku With Short Videos Presentation - Jonizar, Jonizar (Journal of English and Education (JEE), 2010)
This action research was aimed at finding out whether students' speaking ability could be improved by presenting short videos. This research was done at the third year students ofSMAN4 OKU. There were 41 students. This research was carried out by asking the students to present short videos. Other students asked and answer the questions. Before, during and after the action was conducted, the teacher observed and took a note with the help from his collaborator. This action research was conducted in 2 cycles. In each cycle, I did four steps : a. Planning, b. Implementing Action,. Interpreting and, d. Analyzing and Reflecting. Each cycle was done in three weeks, fourty five minutes every week. The research finding showed the students' speaking ability could be improved by presenting short videos. Presentation with short videos could stimulate the students to participate actively in teaching learning activities. Finally, the result of the observation indicated that most of the students were able to speak English with short videos presentation.